Education on the Utilization of Turmeric Decoction to Improve Adolescent Girls' Knowledge of Vaginal Discharge Prevention - Astri Ulina Saragih; Meria Turnip; Rizky Yulanda; Santa Natalia (JURNAL PENGMAS KESTRA (JPK), 2026)
Vaginal discharge is a reproductive health problem frequently experienced by adolescent girls and can impact their comfort, daily activities, and the quality of their reproductive health. The high incidence of vaginal discharge in adolescents is often influenced by a lack of knowledge regarding personal hygiene of reproductive organs and the limited use of herbal ingredients as a preventative measure. Turmeric (Curcuma longa L.) is an herbal plant containing curcumin compounds that have antioxidant, anti-inflammatory, and antimicrobial activities, thus potentially supporting women's reproductive health. This community service activity aims to increase adolescent girls' knowledge about preventing vaginal discharge through education on the use of turmeric water decoction at MAS SKB 3 Menteri Bingkat, Serdang Bedagai Regency. The implementation method includes reproductive health counseling, distribution of educational media in the form of leaflets, demonstrations of making turmeric water decoction, and evaluation of knowledge levels using pre-test and post-test instruments. The activity was carried out in February 2026 with 35 adolescent girls as participants. The evaluation results showed an increase in knowledge after the education was provided, as indicated by an increase in the average knowledge score from 58.3 in the pre-test to 86.7 in the post-test. Furthermore, participants demonstrated active participation throughout the activity and understood the benefits and how to use turmeric water decoction as a preventative measure against vaginal discharge. Therefore, reproductive health education combined with a demonstration of the use of turmeric water decoction was effective in increasing adolescent girls' knowledge about preventing vaginal discharge. This activity can be used as an alternative promotional strategy to support improving adolescent reproductive health in schools